Implementation of Diagnostic Strategies in Arabic Language Learning - Afriati, Intan; Nasafaril, Annisa; Tsaqiyya, Awfa; Al-Afkari, Luthfi (Indonesian Journal of Education and Social Humanities, 2025)
This study discusses the application of diagnostic strategies in Arabic language learning. Diagnostic strategies are an essential learning approach in Arabic language teaching. This approach allows teachers to design teaching that is adaptive and based on student needs. Proper diagnosis will result in more meaningful learning and optimal learning outcomes. The advantages of this approach are that if the learning material is mastered by students or cannot be seen so that it is easier to identify it and the method used to overcome students who do not understand the concept well, while the disadvantage lies in the long preparation, requiring specific teacher skills, limited availability of tools and instruments and suboptimal further implementation. Diagnostic strategies can increase learning motivation because students feel helped according to their needs, encourage active and reflective learning, reduce the rate of errors in language use, both oral and written, and accelerate the achievement of basic language learning competencies.